Outbreak of Anthrax in the Yamalo-Nenets Autonomous District in 2016, Epidemiological Peculiarities - A. Yu. Popova; Yu. V. Demina; E. B. Ezhlova; A. N. Kulichenko; A. G. Ryazanova; V. V. Maleev; A. A. Ploskireva; I. A. Dyatlov; V. S. Timofeev; L. A. Nechepurenko; V. V. Khar’kov; А. Ю. Попова; et al. (Problems of Particularly Dangerous Infections, 2016)
In 2016, in the territory of Yamalo-Nenets Autonomous District an outbreak of anthrax took place, 2650 reindeers were infected. As a consequence of contacts with affected and fallen animals, 36 cases of human infection occurred, of which one was fatal. Performed full-extent complex of anti-epidemic, anti-epizootic, and preventive measures, prompt organization of operations at the regional level allowed for localization of large-scale anthrax focus within the minimum possible time. Based on the lessons learned, identified were the ways to further enhancement of epidemiological surveillance and prophylaxis of anthrax under current conditions. В 2016 г. на территории Ямало-Ненецкого автономного округа возникла эпидемия сибирской язвы, при этом заболело 2650 северных оленей. В результате контакта с больными и павшими животными заболело 36человек с одним летальным исходом. Проведенный в полном объеме комплекс противоэпидемических, противоэпизоотических и профилактических мероприятий, оперативная организация работы на региональном уровне позволили в максимально короткие сроки локализовать крупный очаг сибирской язвы. На основании опыта работы во время вспышки определены пути дальнейшего совершенствования эпидемиологического надзора и профилактики сибирской язвы в современных условиях.